Evaluation of organ at risk (OAR) doses based on 2D treatment planning in intracavitary brachytherapy of cervical cancer - Reduan Abdullah; Nur Aqilah Abdul Sani; Chen, Suk Chiang; Mazurawati Mohamed; Nik Ruzman Nik Idris; Ahmad Lutfi Yusoff; Bhavaraju VMK (Universiti Kebangsaan Malaysia, 2015)
Conventional two-dimensional (2D) treatment planning of intracavitary brachytherapy is still a common practice at the radiotherapy center. The purpose of this study was to evaluate the organ at risk (OAR) doses estimated based on International Commission on Radiation Units and Measurements (ICRU) reference-point in patients with cervical cancer treated with high-dose-rate (HDR) intracavitary brachytherapy (ICBT). Between January 2010 and April 2014, 21 cervical cancer patients were treated with 42 fractions of brachytherapy using tandem and ovoids and underwent post-implant two-dimensional (2D) radiograph scans. HDR brachytherapy was delivered to a dose of 18 Gy in two fractions. Using the Oncentra brachytherapy treatment planning system (BTPS) software version 4.1 (Nucletron, Netherlands), the bladder and rectum points were retrospectively reconstructed based on 42 orthogonal radiographs datasets. The ICRU bladder and rectum point doses were recorded. As for results, the mean percentage dose of rectum and bladder for selected patients treated with intracavitary brachytherapy treatment (ICBT) were 47.27 and 75.59%, respectively. Combinations of ovoid’s size, length of tandem and anatomy variation between each patient were factors that affected the dose to the OAR. Therefore, the ICRU reference points can still be used with the 2D brachytherapy treatment planning in evaluating the OAR doses.